Kesiapsiagaan Darurat Pada Anak Penyandang Disabilitas Dalam Menghadapi Bencana Alam di Sekolah - Firstika Nabilla Balqis; Abdurrozzaq Hasibuan (PT. Alahyan Publisher Sukabumi, 2024)
This study aims to examine emergency preparedness for children with disabilities in facing natural disasters at school. The method used is a literature review, analyzing various sources from journals published between 2019-2024. The results show that emergency preparedness in schools is still not optimal, especially for children with disabilities. The main obstacles include the lack of training, minimal disaster risk reduction educational materials, and limited facilities. Furthermore, data collection on students with disabilities who require special attention in emergency situations has not been comprehensively conducted. Schools play a crucial role in forming inclusive and safe preparedness, but this requires support from various parties, including parents and the community. To enhance preparedness, optimizing disaster preparation programs, improving the quality of training and education, providing adequate facilities, and accurate data collection are necessary. With these measures, it is hoped that disaster preparedness in schools can be improved, thereby minimizing the adverse impacts that may occur.